2012
DOI: 10.3389/fpsyg.2012.00393
|View full text |Cite
|
Sign up to set email alerts
|

Mine is Earlier than Yours: Causal Beliefs Influence the Perceived Time of Action Effects

Abstract: When a key press causes a stimulus, the key press is perceived later and the stimulus earlier than key presses and stimuli presented independently. This bias in time perception has been linked to the intention to produce the effect and thus been called intentional binding (IB). In recent studies it has been shown that the IB effect is stronger when participants believed that they caused the effect stimulus compared to when they believed that another person caused the effect (Desantis et al., 2011). In this exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…The third candidate signal relates to prior thought (magenta component in figure 4). Previous studies [9][10][11]38,39] have advocated several principles, such as priority, rspb.royalsocietypublishing.org Proc R Soc B 280: 20130991 consistency and exclusivity as those probably govern the inference of causality between prior thoughts and action/effect. In particular, the principle of exclusivity is compatible with the one-to-one mapping rule observed in experiment 4.…”
Section: Discussionmentioning
confidence: 99%
“…The third candidate signal relates to prior thought (magenta component in figure 4). Previous studies [9][10][11]38,39] have advocated several principles, such as priority, rspb.royalsocietypublishing.org Proc R Soc B 280: 20130991 consistency and exclusivity as those probably govern the inference of causality between prior thoughts and action/effect. In particular, the principle of exclusivity is compatible with the one-to-one mapping rule observed in experiment 4.…”
Section: Discussionmentioning
confidence: 99%
“…Despite deep controversy over the underlying mechanisms, temporal binding has been used as a proxy for the SoA in several studies [4] , [27] , [28] . The link between temporal binding and SoA is bolstered by findings that prior agency beliefs influence the strength of the binding effect [7] , [29] . Furthermore, certain experimental manipulations which modulate the SoA, such as the congruency of action-effects and the valence of outcomes, may also modulate temporal binding [30] , [31] , [32] , [33] ; but see also Desantis et al [34] , who reported that the mere presence of an action was sufficient to induce temporal binding irrespective of the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the present study contributes to a larger understanding of how vantage can systematically bias perceptual experience 7,13,15,[40][41][42] . More broadly, we hope that in time, such findings will cue individuals to consider how differences in judgment may arise from two differing vantages of the same situation, as well as how their own beliefs and experiences have been shaped by their unique perspective.…”
Section: Discussionmentioning
confidence: 68%
“…From lining up a touch and sound so that they feel simultaneous, to temporally binding an action and its delayed effect with causation, our brains are remarkably good at piecing together signals to construct a holistic perception of our world [1][2][3][4][5][6] . However, this temporal integration can oftentimes lead to illusions and misperceptions during narrow temporal intervals [7][8][9][10][11][12][13][14][15] .…”
Section: Egocentric Temporal Order Bias Robust Across Manipulations Omentioning
confidence: 99%